Implementation Of Prompt Ai Assisted By Interactive Games To Strengthen Computational Thinking And Critical Thinking In Indonesian Language Learning Grade Iv Students Of Sd Negeri Karangmloko 1 Ngaglik Sleman - Maria Sri Mulati; Azamul Fadhly Noor Muhammad (Yayasan Azhar Amanaa Yogyakarta, 2026)
The rapid development of technology in the field of education encourages teachers to create innovative and interactive learning processes that are able to strengthen students’ 21st-century skills. This study aims to describe the implementation of Artificial Intelligence prompts assisted by interactive games on the topic of text types in Indonesian language learning to strengthen Computational Thinking and critical thinking skills of fourth-grade students at SD Negeri Karangmloko 1 Ngaglik Sleman. This study employed a descriptive qualitative approach involving fourth-grade students as research subjects. Data were collected through observation, interviews, documentation, and learning activity results. The learning process integrated Artificial Intelligence-based prompts and interactive games to support students in understanding various text types through engaging and technology-supported activities. The findings indicate that the implementation of Artificial Intelligence prompts assisted by interactive games was able to improve students’ participation, learning motivation, and understanding of text-type materials. In addition, the learning activities supported the development of Computational Thinking skills, including problem decomposition, pattern recognition, abstraction, and algorithmic thinking. Students also demonstrated improvements in critical thinking skills through questioning activities, problem-solving, idea analysis, and conclusion drawing during the learning process. Therefore, the integration of Artificial Intelligence prompts and interactive games can serve as an innovative learning strategy to create meaningful, interactive, and student-centered learning in elementary schools. Keywords: Artificial Intelligence, Interactive Games, Computational Thinking, Critical Thinking, Indonesian Language Learning, Text Types.